Enhanced Handoff Scheme for Downlink-Uplink Asymmetric Channels in Cellular Systems. (31st December 2013) - Cho, Sunghyun; Kim, Ji-Su; Kim, Jae-Hyun
Abstract : In the latest cellular networks, data services like SNS and UCC can create asymmetric packet generation rates over the downlink and uplink channels. This asymmetry can lead to a downlink-uplink asymmetric channel condition being experienced by cell edge users. This paper proposes a handoff scheme to cope effectively with downlink-uplink asymmetric channels. The proposed handoff scheme exploits the uplink channel quality as well as the downlink channel quality to determine the appropriate timing and direction of handoff. We first introduce downlink and uplink channel models that consider the intercell interference, to verify the downlink-uplink channel asymmetry. Based on these results, we propose an enhanced handoff scheme that exploits both the uplink and downlink channel qualities to reduce the handoff-call dropping probability and the service interruption time. The simulation results show that the proposed handoff scheme reduces the handoff-call dropping probability about 30% and increases the satisfaction of the service interruption time requirement about 7% under high-offered load, compared to conventional mobile-assisted handoff. Especially, the proposed handoff scheme is more efficient when the uplink QoS requirement is much stricter than the downlink QoS requirement or uplink channel quality is worse than downlink channel quality.